Lightning Surge Damage in PoE Ethernet Links: A Boyolali Tower Case Study - Yuwono Bimo Purnomo; Fajar Budi Setiawan; Khampaserth Xaphakdy (Jurnal Teknik Elektro dan Informatika, 2026)
Lightning surge damage in hybrid power and communication infrastructures remains a critical issue in tropical regions with high lightning activity. This case study investigates network equipment failure following a thunderstorm-induced power outage exceeding 24 hours in Boyolali, Central Java, Indonesia. The system comprises a 28 m communication tower connected to a server building via a 15 m outdoor unshielded twisted-pair (UTP) Ethernet cable utilizing Power-over-Ethernet (PoE). The tower employs a dedicated lightning-protection grounding system, while the building uses a separate electrical grounding system separated by approximately 10 m and left unbonded. Post-incident inspection revealed that four networking devices were damaged: one PoE injector and one MikroTik CRS326 switch at the tower site, plus one MikroTik CRS326 and one D-Link DGS-1100-24 switch at the server building. The Dell PowerEdge R360 server remained operational after a manual restart. Failure analysis indicates that the damage resulted from surge propagation caused by ground potential rise (GPR) at the tower grounding system. The unbonded grounding systems and the conductive copper PoE link provided a low-impedance path for transient currents. This study highlights the importance of coordinated grounding, surge protective devices (SPDs), and the preference for optical fiber links in hybrid infrastructures. The findings offer practical insights for enhancing lightning protection in tropical communication systems.